Impact of planning and building regulations on affordable housing development by the private sector in South Africa - Ekpo, Christiana (Department of Construction Economics and Management, 2020)
This study emerged from existing literary evidence that planning and building regulations affect the supply of housing and research in this area usually takes a very descriptive route that lacks an explicit theoretical framework that can guide stakeholders for better research outcomes. The rationale is based on the context that despite the many initiatives introduced by successive post-apartheid governments to improve the housing situation in South Africa, not much has been achieved to improve the enormous housing backlogs. Affordable housing, being one of the strategic mechanisms used by the government for housing delivery is laden with problems. Many factors have been attributed to the challenges among which are land use policies and building regulations, administrative bottlenecks, budgetary constraints, and so on. To effectively manage these challenges, a more proactive private sector participation has been advocated. However, this requires that proper regulatory frameworks are put in place to ensure that developers deliver housing that meets necessary safety and quality standards and still have some return on investment. Unfortunately, legislative structures which should ideally be supportive, instead, hinder development and create barriers for private developers The study thus investigates three related questions. Firstly, what are the main planning and building regulations that impact on affordable housing by the private sector? Secondly, how do the planning and building regulations affect the total cost of affordable housing development by the private sector? Thirdly, what scope exists for the change and would, relaxing these regulations, enhance the supply of affordable housing developments by the private sector in South Africa? Corresponding to these questions is the first hypothesis which states that planning and building regulations impose a significant cost on the developers and thus deter the supply by the private sector. And secondly, relaxing some of the planning and building regulations could improve affordable housing development by the private sector. The study employed a qualitative approach to gather empirical data using household surveys and semi-structured interviews from developers and consultants on five case studies together with key informants’ interviews from government officials. With the main theoretical tools of Institution Analysis and Development, this study developed a conceptual framework that determines the main planning and building regulations that impact on affordable housing supply by the private sector. And by employing insights from New Institutional Economics tools, these regulations are treated as institutions through which development rights are obtained. The study reveals; that even though planning and building regulations are affiliated with better quality housing products, they significantly affect cost, affordability and location outcomes. That no national policy tool exists to guide affordable housing implementation processes; the current city’s policy instruments are contradictory to the propagated concepts meant to enhance housing supply. The study discovers that the government has huge land parcels for different intentions, but makes it available only to a developer whose objectives align with theirs and developers lack adequate funding and incentives to motivate them. Finally, the study reveals that even when case studies are located outside the urban core of Cape Town, dwellers are happy and satisfied with the location and careless about the system’s inefficiencies and there is no direct relation between planning and building regulations and location other than the fact that regulations contribute to the bad location of developments.